Makna Simbolik Adat Bakayab Hai di Desa Pelita Jaya Kepulauan Sula - Sidik Dero Siokona; Fadila Umasugi (Peneliti.net, 2022)
This research was conducted with the aim of describing the stages of implementation of the Bakayab Hai custom as well as the meanings and symbols in the Bakayab Hai custom. This study used a qualitative research method which was conducted in Pelita Jaya Village, North East Mangoli District, Sula Islands Regency for three months, namely from December 2021 to February 2022. The techniques used to collect research data were observation, interviews, and documentation. Research data analysis techniques are qualitative descriptions. The results of the study prove that the stages in the bakayab hai custom are, a) basoa li/propose marriage, b) the first proposal, (meaning kedangan from the male side), c) the second proposal (preparation of ingredients in the form of siri, areca nut, and lime), d ) third proposal (breaking li madas), e) basalwir (balelyan), f) badaka (using powder), g) qabul gem nap (holding head), h) fate (eating together), i) sekapur siri (expression of the heart ) j) bridal delivery, k) pin uba (carrying), l) gia el (eating areca nut), m) bakayab hai (stepping on the ground). The traditional symbolic meaning of Bakayab Hai, a) land, meaning the origin of human creation and the return of humans to death, b) a cone-shaped pile of earth, the meaning is the initial stage of life, c) water means holy, d) leek/karua grass means fertility, e ) half a dozen plates mean offspring, f) colorful flowers mean colorful life.